Analysis of E-Government Implementation as an Effort to Reduce Corruption in Indonesia - Hadmar, Ahmad Muhardin; Madamang, Irwan (Arus Jurnal Sosial dan Humaniora, 2025)
This research aims to analyze the impact of implementing e-government on reducing corruption in Indonesia. Analysis was carried out using qualitative methods through a narrative observation process. Research data was collected from various trusted sources, such as the E-Government Development Index (EGDI), Transparency International (TI), and Worldwide Governance Indicator (WGI). The analysis revealed three main indicators, namely e-government development, government effectiveness, and anti-corruption education. The research results show that there is minimal impact of e-government in preventing corruption in Indonesia. Based on EGDI data, in 2022 Indonesia's ranking will increase significantly to reach the 77th position. However, Indonesia Corruption Watch (ICW) noted a decline in investigations into corruption cases. This occurred as a result of the revision of Law Number 19 of 2019 which had an impact on the independence of the Corruption Eradication Commission (KPK). Additionally, TI noted a drastic decline in perceptions of corruption in Indonesia, while WGI data showed a decline in the effectiveness of public sector officials. In this context, anti-corruption education through e-learning programs is a crucial factor in building community integrity. This study emphasizes the importance of evaluating anti-corruption policies, the independence of the KPK, and e-learning-based anti-corruption education in Indonesia.